Losses from horizontal merger and collusion - Hamid Beladi; Arijit Mukherjee (Journal of Economics, 2024)
Abstract We show that the implications of a merger on collusion sustainability change significantly from the extant literature if merger is not profitable in the punishment subgame where firms play non-cooperative Cournot–Nash game. Merger either does not affect collusion sustainability or it may decrease or increase collusion sustainability, depending on the output allocation for the merged firm. Our paper has the following implication for antitrust policies. If merger is observed, the authority will expect an industry-wide collusion, since merger will occur in our analysis provided it increases collusion sustainability.
Additional information: D21;D43;D45;L13
Keywords: 330; Collusion; Cournot–Nash; Merger